29. ERP generators in an omitted-target oddball task: A simultaneous EEG-fMRI study. Issue 12 (December 2016) - Di Rollo, A.; Cosottini, M.; Pesaresi, I.; Fabbri, S.; Di Russo, F.; Perri, R.L.; Barloscio, D.; Bocci, T.; Ragazzoni, A.; Sartucci, F.
Abstract : This study investigated the cerebral sources of the visual event-related potential (ERP) with the help of simultaneous recording of functional magnetic resonance imaging (fMRI). As tasks, in addition to a standard two-stimuli visual "oddball" paradigm, we applied a similar paradigm, in which the rare (target) stimuli were omitted in a sequence of regularly presented visual stimuli. Pre-stimulus ERP showed larger prefrontal activity over the righ hemisphere in the omitted-target task. Post-stimulus ERP showed a clear P1/N1/P2/Pp2/P3 complex during the standard "oddball" paradigm, whereas during the "omitted target" task, only the Pp2 and P3 components were present. The P3 was reduced amplitude and increased latency (from 450 to 520 ms). fMRI showed, during both tasks, activations in lateral frontal, fronto-operculum, anterior insula regions, prevailing on the right. Minor activations were observed bilaterally in the parietal cortex near the intraparietal sulcus and in posterior temporal regions, also more evident on the right hemisphere. The "omitted task" paradigm showed larger fMRI activations in prefrontal areas. These results showed for the first time the strong top-down preparatory cognitive control in the "omitted target" task and highlight the endogenous nature of P3.